EFFECT OF COTTON DUST EXPOSURE ON RESPIRATORY HEALTH OUTCOMES AMONG TEXTILE WORKERS - Afreen Sadia,; Yousaf Ali,; Hasan Nawaz Tahir,; Natasha Shaukat,; Muhammad Irfan,; Nafees, Asaad Ahmed (Journal of Ayub Medical College Abbottabad, 2023)
Background: Cotton dust is generated during various textile manufacturing processes. Only a few studies from Pakistan assessed cotton dust exposure and explored the relationship of duration of work in the textile industry with respiratory health outcomes. We aimed to assess cotton dust exposure and its association with lung function and respiratory symptoms among textile workers in Pakistan. Methods: We report findings from the baseline cross- sectional survey of the larger study, MultiTex, among 498 adult male textile workers from six mills conducted between Oct 2015-March 2016 in Karachi, Pakistan. Data collection included the use of standardized questionnaires; spirometry, and area dust measurements through UCB-PATS. Multivariable logistic and linear regression models were developed to assess the association of risk factors with respiratory symptoms and illnesses. Results: We found the mean age of workers to be 32.5 (±10) years; around 25% were illiterate. The prevalence of COPD, asthma, and byssinosis in our study was 10%, 17%, and 2%, respectively. The median cotton dust exposure was 0.33 mg/m3 (IQR;0.12-0.76). Increased duration of work among non-smokers was associated with a decline in lung function, FVC (-245 ml; 95% CI -385.71, -104.89) and FEV1 (-200 ml; 95 % CI -328.71, -84.11). Workers with certain job titles (machine operators, helpers, and jobbers), those with greater duration of work, and higher dust exposure, were more likely to report respiratory symptoms and illnesses. Conclusion: We report a high prevalence of asthma and COPD and a low prevalence of byssinosis. Cotton dust exposure and duration of employment were associated with respiratory health outcomes. Our findings highlight the need for preventive interventions in the textile industry in Pakistan.